The COVID-19 Pandemic and its Impact on the Banking Industry – A Case of National Bank Ltd. - Mohania, Sarvesh; Mainrai, Girish (Indian Journal of Finance, 2020)
The COVID-19 or Novel Coronavirus pandemic has impacted every sector of the economy. The banking sector is no exception, which is facing multitude of challenges. Some of the challenges are generic in nature like contraction of demand for products and services, restriction in mobility, logistics, and even sustainability in the present scenario. Some of these are sector specific, like the banking sector is facing a number of challenges with regard to operations, asset quality, and earnings to name a few. National Bank, which recently successfully handled the merger of Sagar Bank Ltd. in its fold, faced another big challenge in the form of this pandemic. Apart from the generic challenges mentioned above, National Bank is confronted with other challenges like employee morale, liquidity, and vendor management. Management of National Bank realized that it has to formulate specific strategies in order to deal with the circumstances arising on account of this pandemic. The management, being fully aware of the bank's weaknesses and looking into the threats posed by this pandemic, wanted to devise strategies catering to the circumstances. The CMD (Chairman & Managing Director) of National Bank elicited feedback of all CGMs (Chief General Managers) for dealing with the ramifications of this pandemic. The senior management soon realized that it has to act swiftly in order to minimize the impact of this pandemic on the bank.